2003
DOI: 10.1507/endocrj.50.289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ghrelin on Growth Hormone Secretion from Cultured Adenohypophysial Cells in Cattle

Abstract: To clarify the direct effects of ghrelin on growth hormone (GH) release from anterior pituitary (AP) cells in cattle, GH-releasing effects of human ghrelin (hGhrelin) and rat ghrelin (rGhrelin) on bovine AP cells were compared with those of GH-releasing hormone (GHRH) in vitro. The AP cells were obtained from Holstein steers and were incubated for 2 h with the peptides after incubating in DMEM for 3 days. hGhrelin and rGhrelin significantly stimulated GH release from the cultured cells at doses from 10(-10) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In a perfusion system, GHRH and ghrelin stimulated GH release from isolated rat anterior pituitary cells in a dose-dependent manner at doses from 10 -10 to 10 -8 M [20]. Hashizume et al found that these peptides directly stimulate GH release from static cultured bovine anterior pituitary cells [21]. The present study used a static incubation system.…”
Section: Discussionmentioning
confidence: 73%
“…In a perfusion system, GHRH and ghrelin stimulated GH release from isolated rat anterior pituitary cells in a dose-dependent manner at doses from 10 -10 to 10 -8 M [20]. Hashizume et al found that these peptides directly stimulate GH release from static cultured bovine anterior pituitary cells [21]. The present study used a static incubation system.…”
Section: Discussionmentioning
confidence: 73%
“…In a preliminary study, we found that human ghrelin also stimulates GH release from dispersed pituitary cells in vitro (unpublished observations), adding more support for our present findings. Ghrelin stimulates GH release from the dispersed pituitary cells of rats (23,38), pigs (11), and cattle (12). Stimulatory effects of ghrelin on GH release were also reported from studies using the incubated whole pituitaries of tilapia (20,39), eel (19), and trout (18).…”
Section: Effects Of Ghrelin On Lh and Gh Releasementioning
confidence: 76%
“…It is known that ghrelin stimulates GH release from anterior pituitary cells (Kojima et al 1999, Yamazaki et al 2002, Hashizume et al 2003, Malagon et al 2003, and several recent studies have indicated that this effect is mediated via not only the direct, but also the indirect pathways, including the vagal afferent nerve (Date et al 2002, Sakata et al 2003. In addition to GH release, ghrelin also stimulates food intake and adiposity in humans and rodents (Tschop et al 2000, Wren et al 2000, Asakawa et al 2001, Shintani et al 2001, indicating that these physiological effects of ghrelin play an important role in growth regulation and energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%